Legal Disharmony in Filling the Village Head Position Following Temporary Suspension in Sidoarjo - Putri Pangesti, Mayang (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2025)
Village governance demands stable leadership to ensure the effective delivery of public services and development execution. However, a critical legal issue arises when a Village Head is temporarily suspended due to corruption charges, creating a transitional leadership vacuum. This study aims to comprehensively analyze the legal vacuum (lacuna legis) and regulatory disharmony regarding the filling of the Village Head position following temporary dismissal in Sidoarjo Regency, and to investigate the consequent socio-legal implications on village administration stability. The novelty of this research lies in its distinct focus; while existing literature largely discusses the criminal liability of corrupt village heads or the administrative procedures of dismissal, this study specifically isolates the